“We do not like it but it has to be done”: How temporal personality and team improvised adaptation can foster team performance - Abrantes, A.; Passos, A. M.; Cunha, M. P.; Miner, A. (EURAM 2019 Conference, 2019)
Objective: Turbulent business environments require responsive teams able to rapidly react to an unpredictable change. The type of team capable of such responsiveness, and how it responds, requires better exploration. This study investigates the role played by team temporal personality in a team’s ability to perform well when a disruption occurs, and time is so scarce that planning and execution need to be concurrent. Method: In a laboratory setting, 180 full-time workers randomly assigned to 60 teams were assessed on their present- and future-orientation personality traits, and evaluated on their ability to adapt under disruptive and time-constrained situations. Fifty-three percent of all participants were women and the average age was forty. Results: The results show that when an unpredictable disruption arises and the time available is quite scarce, the elevation of team future orientation positively affects team performance through team improvised adaptation. The findings also reveal that in such conditions, team future-orientation diversity limits a team’s ability to perform well. Conclusions: This work contributes to our understanding of the role that team temporal personality plays in a team’s ability to deal with unpredictability and temporal scarcity. In particular, the study reveals the different influences of diversity and elevation of future orientation on team performance in such contexts. It also suggests that these effects operate through team improvised adaptation.